Effect of Fetal Delivery on Pao2/Fio2 Ratio During Mechanical Ventilation in Parturients With COVID-19: A Case Series. Issue 7 (25th July 2022) - Kodali, Bhavani Shankar; Wong, Michael J.; Lankford, Allison; Lee, Khang; Bharadwaj, Shobana
Abstract : It is controversial whether fetal delivery improves maternal oxygenation during mechanical ventilation. We evaluated maternal arterial partial pressure of oxygen (Pao 2 ) to fractional oxygen concentration (Fio 2 ) (P/F) ratios before and after delivery in this series of 15 parturients with coronavirus disease 2019 (COVID-19). Compared to the immediate postpartum period, P/F ratio was increased at 48 hours (212 ± 101 vs 271 ± 90; P = .006). Linear regression demonstrated improvement in P/F ratio during the study period (slope, 3.1; 95% confidence interval [CI], 0.87–5.34; P = .007), although predelivery and postdelivery periods separately did not exhibit any specific trend. Five patients required emergent bedside delivery. We discuss numerous considerations guiding delivery planning during mechanical ventilation.